2022
DOI: 10.4103/jfmpc.jfmpc_2103_21
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy after taking the first dose of COVID-19 vaccine

Abstract: Background: Coronavirus disease 2019 (COVID-19) vaccination campaigns are trying to curb the pandemic by vaccinating as many individuals and as quickly as possible. The speed of immunization depends upon the availability of the vaccine and vaccine uptake by the communities, which in turn is related to vaccine hesitancy, the safety/efficacy profile of the vaccines, and adverse events following immunization (AEFI) Objectives: (i) To study the AEFI experienced by vaccine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…3, September 2023: 924-931 930 the AEFI incidence of the COVID-19 vaccine at doses 1 and 2 was comparable to the trial results and in the community [27]. Other studies, on the other hand, found that because they had AEFI at dose 1, people were hesitant to receive dose 2 [9], [16], [28], [29].…”
Section: Discussionsupporting
confidence: 54%
“…3, September 2023: 924-931 930 the AEFI incidence of the COVID-19 vaccine at doses 1 and 2 was comparable to the trial results and in the community [27]. Other studies, on the other hand, found that because they had AEFI at dose 1, people were hesitant to receive dose 2 [9], [16], [28], [29].…”
Section: Discussionsupporting
confidence: 54%
“…Hence, a subgroup analysis was conducted based on the gender and residence that might differ significantly across the studies. Additionally, M et al [27] SJ et al [28] M et al [29] SA et al [30] r GC et al [31] N et al [32] ta S et al [33] S et al [34] a P et al [35] a Y et al [36] A et al [37] S et al [38] N et al [39] l Y et al [40] arathi A et al…”
Section: Discussionmentioning
confidence: 99%
“… Acceptance of the COVID-19 vaccine in India according to residence, as shown in the form of a forest plot [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. …”
Section: Figurementioning
confidence: 99%
“…This may include mild fever and shoulder pain after 12-48 hours of immunization [15] . A recent study conducted in India on the assessment of vaccine hesitancy after taking the first dose of COVID-19 provides evidence for vaccine reluctance to second dose due to post-immunization adverse events [16] . Recent data collected in Saudi Arabia proved that 24.1% of people were hesitant based on the long waiting hours experienced at vaccination centers [17] .…”
Section: Booster Dose Hesitancymentioning
confidence: 99%